(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Competency based medical education • Focus of curriculum: Competencies are clearly defined and that needs to be achieved at the end of training. • Structure and content of curriculum: CBME is paced. • Goal: Knowledge application. • Learning style: Teachers and learners are both equally involved. • Logistics of training Implementation: CBME it is not time bound. • Assessment: Assessment is based on Formative assessment, feedback and is criterion referenced. Assessment is by multiple tools, multiple assessors, multiple times, longitudinal and frequent. Lot of emphasis is on authentic work-based assessment under direct observation.